Electron-Stimulated Hydrogen Desorption from Nickel and Palladium; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 12, No. 1 - Tyurin Yu. I. Yuri Ivanovich; Chernov I. P. Ivan Petrovich; Silkin V. M. Vyacheslav Mikhaylovich; Sypchenko V. S. Vladimir Sergeevich; Khashkhash A. M. Adel Mokhammed; Nikitenkov N. N. Nikolai Nikolaevich; Tolmacheva N. D. Nella Dmitrievna (2018, 2018)
Title screen